People's Republic of China : Detailed Assessment Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses the key findings of the assessment of the current state of the implementation of the Basel Core Principles for Effective Banking Supervision in China. China's legal framework sets clear responsibilities and objectives for banking supervision in China. Overall, China Banking Regulatory Commission's (CBRC) legal mandate and responsibilities, supported by broad powers, enables CBRC to conduct banking supervision in an effective way, with a primary focus on safety and soundness. A comprehensive set of regulations and procedures have provided CBRC with the necessary tools to properly operationalize its mandate, while strong enforcement powers further support the effectiveness of supervisory actions. Cooperation and collaboration with local and foreign authorities are also in place.